Towards a Pattern Language for Networked Learning - Goodyear, Peter; Avgeriou, Paris; Baggetun, Rune; Bartoluzzi, Sonia; Retalis, Simeon; Ronteltap, Frans; Rusman, Ellen (Proceedings of the International Conference on Networked Learning, 2004)
The work of designing a useful, convivial networked learning environment is complex and demanding. People new to designing for networked learning face a number of major challenges when they try to draw on the experience of others – whether that experience is shared informally, in the everyday language of educational practice, or through published research and evaluation studies, or through sets of action-oriented guidelines. In this paper we present a novel approach to sharing educational design experience, making use of an organisational and communicative framework derived from Christopher Alexander’s work on pattern languages. We describe the structure and purpose of design patterns, show how they fit together in a pattern language, and illustrate the approach with reference to some design patterns for networked learning. For clarity, our presentation is set within a specific conception of the nature of designing for networked learning, but we aim to show how the patterns-based approach transcends such particularities. We suggest that design patterns offer a useful method for sharing design ideas in participatory educational design work.